Asking The Right Questions; Tips and Suggestions for Psychiatric Interview for Medical Students - Ang, Ai Ling (UNIMAS Publisher, 2020)
Getting accurate information about human experiences and events is crucial for professions like lawyer, police officer and doctor, where specialized interviewing techniques form an essential part of their training, although the interview techniques and focus varies in these professions.